2014
DOI: 10.1158/0008-5472.can-13-2730
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibody Targeting of the Cell Surface Molecule TM4SF5 Inhibits the Growth of Hepatocellular Carcinoma

Abstract: The cell surface transmembrane receptor TM4SF5 has been implicated in hepatocellular carcinoma (HCC), but its candidacy as a therapeutic target has not been evaluated. Building on findings that immunization with a peptide vaccine targeting human TM4SF5 can exert prophylactic and therapeutic effects in a murine model of HCC, we developed a monoclonal antibody to characterize expression of TM4SF5 in HCC and to target its function there as an anticancer strategy. We found that the antibody modulated cell signalin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(43 citation statements)
references
References 33 publications
3
40
0
Order By: Relevance
“…We previously showed that the anti-TM4SF5 antibody induced changes in actin polymerization and formation of focal adhesion sites in HCC cells based on phalloidin and paxillin staining [42]. However, we found that there was no change in colon cancer cells (data not shown).…”
Section: Resultsmentioning
confidence: 55%
See 2 more Smart Citations
“…We previously showed that the anti-TM4SF5 antibody induced changes in actin polymerization and formation of focal adhesion sites in HCC cells based on phalloidin and paxillin staining [42]. However, we found that there was no change in colon cancer cells (data not shown).…”
Section: Resultsmentioning
confidence: 55%
“…Previously, we found that treatment of HCC cells expressing TM4SF5 with anti-TM4SF5 antibody enhances expression of E-cadherin [42]. We therefore checked expression of E-cadherin using confocal microscopy and Western blotting analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was passaged for less than 6 months after receipt and used in spiking experiments of the current study. The cell line was characterized by the cell bank based on cell morphology, post-freeze viability, isoenzyme analysis, DNA fingerprinting analysis, mycoplasma contamination test, and bacterial and fungal contamination (33). The cell line was maintained in DMEM (Gibco) supplemented with 10% FBS…”
Section: Cell Linementioning
confidence: 99%
“…We found TM4SF5, which was over-expressed in gastric cance r (Tab. 2), which was also over-expressed in other kinds of cancer (23)(24)(25)(26), so drew the CNC network between TM4SF5 and LncRNAs by PCC (Fig. 4a).…”
Section: Construction Of the Coding-non-coding Gene Co-expression Netmentioning
confidence: 99%